2022
DOI: 10.1038/s41467-022-33873-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased susceptibility of Plasmodium falciparum to both dihydroartemisinin and lumefantrine in northern Uganda

Abstract: Artemisinin partial resistance may facilitate selection of Plasmodium falciparum resistant to combination therapy partner drugs. We evaluated 99 P. falciparum isolates collected in 2021 from northern Uganda, where resistance-associated PfK13 C469Y and A675V mutations have emerged, and eastern Uganda, where these mutations are uncommon. With the ex vivo ring survival assay, isolates with the 469Y mutation (median survival 7.3% for mutant, 2.5% mixed, and 1.4% wild type) and/or mutations in Pfcoronin or falcipai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…Our study did not identify any known pfk13 artemisinin resistance-conferring mutations, confirming that parasites in Zanzibar remain sensitive to the current first-line treatment ASAQ. The recent identification of pfk13 mutants (R561H, C469Y/F, and A675V) in mainland Tanzania 11,23 and neighboring countries Rwanda 26 and Uganda 25 , and the high prevalence of mutations in other drug resistance markers found in this study highlights the need for continued monitoring. Of note, the recently described mutations in the pfk13 gene found in Rwanda, Uganda, and mainland Tanzania were not covered by our panel.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our study did not identify any known pfk13 artemisinin resistance-conferring mutations, confirming that parasites in Zanzibar remain sensitive to the current first-line treatment ASAQ. The recent identification of pfk13 mutants (R561H, C469Y/F, and A675V) in mainland Tanzania 11,23 and neighboring countries Rwanda 26 and Uganda 25 , and the high prevalence of mutations in other drug resistance markers found in this study highlights the need for continued monitoring. Of note, the recently described mutations in the pfk13 gene found in Rwanda, Uganda, and mainland Tanzania were not covered by our panel.…”
Section: Discussionmentioning
confidence: 64%
“…Further, it is crucial to monitor markers of malaria drug resistance. There is increasing evidence of parasites with markers of artemisinin partial resistance circulating in sub-Saharan Africa, including mainland Tanzania, Rwanda and Uganda, threatening the long-term effectiveness of ACT regimens, the current first-line treatment in Zanzibar 11,[23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…It is feasible to speculate that the PfCYP19B upregulation can be co-selected with the genetic alterations (both SNPs and/or transcript upregulation) of the falcipain genes in expression quantitative trait loci (eQTL)-like manner giving it a stronger selective advantage. In future studies it will be interesting to investigate pfcyp19b eQTL linkages with falcipain but also other genes such as coronin, that are currently emerging as new markers of artemisinin resistance [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include mutations in the main hemoglobinase enzymes such as falcipain 2a/b and 3 whose genes are nearest genomic neighbors of pfcyp19b (S9 Fig) . Falcipain genes (or their genetic alterations) were shown to drive artemisinin resistance in vitro using both forward and reverse genetic studies [40,80]. Moreover, their exonic mutation(s) and altered expression were also linked with artemisinin resistance in clinical isolates [31,81]. It is feasible to speculate that the PfCYP19B upregulation can be co-selected with the genetic alterations (both SNPs and/or transcript upregulation) of the falcipain genes in expression quantitative trait loci (eQTL)-like manner giving it a stronger selective advantage.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Further studies have shown that Eastern Africa has become the center of ART-R emergence with multiple validated K13 mutations, 469Y (Uganda), 561H (Rwanda), 622I (Eritrea and Ethiopia) and 675V (Uganda), independently emerging and spreading across borders to neighboring countries. In Uganda, clinical studies and detailed prevalence data over time show 675V and 469Y have increased over time and are now highly prevalent in multiple areas (4,(10)(11)(12)(13)(14). In Eritrea and Ethiopia, 622I are increasing in prevalence (5,15).…”
Section: Introductionmentioning
confidence: 99%